Educational heiditistic model in the development of mathematical competition number and operations - Huilca Flores, María Elena (2018)
The purpose of the research was to determine the effect of the application of a Didactic Model based on the Heuristic Methodology in the development of mathematical competence Number and operations of Fifth grade students of the Educational Institution "Nuestra Señora del Pilar "Of the San Martín de Piura Human Settlement.The research is part of the explanatory studies, with a quasi-experimental design, because it was developed using intact groups, with a population of 140 subjects: 74 students from 5th grade. Degree "A" and "B", of the Educational Institution "Nuestra Señora del Pilar" (Experimental Group), 69 students of the same grade "C" and "D" of the Educational Institution (Control Group).The two groups were given a written Mathematics test consisting of six questions assessing abilities: Matematiza, represents, communicates, uses, elaborates and argues corresponding to the first domain of competence Number and operations, seeking to answer the question: To what extent will the application of a didactic model based on the heuristic methodology contribute to the development of the mathematical abilities of the students of Fifth grade of primary education of the educational institution "Our Lady of the Pillar" of Piura 2014? The study concluded that the didactic model based on the heuristic methodology contributed significantly to the development of the mathematical skills of Fifth grade students of the "Nuestra Señora del Pilar" Educational Institution.